Cultural Differences in Perceiving Sounds Generated by Others: Self Matters - Cao, Liyu; Gross, Joachim (Frontiers in Psychology, 2015)
Sensory consequences resulting from own movements receive different neural processing compared to externally generated sensory consequences (e.g., by a computer), leading to sensory attenuation, i.e., a reduction in perceived loudness or brain evoked responses. However, discrepant findings exist from different cultural regions about whether sensory attenuation is also present for sensory consequences generated by others. In this study, we performed a cross culture (between Chinese and British) comparison on the processing of sensory consequences (perceived loudness) from self and others compared to an external source in the auditory domain. We found a cultural difference in processing sensory consequences generated by others, with only Chinese and not British showing the sensory attenuation effect. Sensory attenuation in this case was correlated with independent self-construal scores. The sensory attenuation effect for self-generated sensory consequences was not replicated. However, a correlation with delusional ideation was observed for British. These findings are discussed with respects to mechanisms of sensory attenuation.